A construção identitária do povo tabatinguense: um olhar para a cidade de fronteira - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This work sought to verify the way in which the identity of the people of Tabatinga - AM is being built, pointing out the sociocultural processes experienced in the border context of a transit city. Understanding the process of identity construction of the Tabatingu people, the research was guided by theoretical contributions from Anthropology, Sociology, Philosophy, Art and Sociolinguistics. Starting from the premise of the analysis of the identity construction of the people of Tabatinga, our research will have a qualitative bias, without discarding the quantitative items that are necessary to understand the data obtained, since they are complementary to the work in the field of social sciences (MINAYO, 1996); (GOLDENBERG, 2015), as well as the in-depth interview (Bourdieu, 2007). The integration of quantitative and qualitative research will allow conclusions to be crossed in order to have greater confidence that the data are not the product of a specific procedure or a particular situation. In this way, it is under these ethodological aspects that we intend to develop our investigation seeking to build, as close as possible, an interpretive framework of the reality in which our object of study is inserted, the identity construction of the Tabatinguense people.

Este trabajo buscó verificar la forma en que se está construyendo la identidad del pueblo de Tabatinga - AM, señalando los procesos socioculturales vividos en el contexto fronterizo de una ciudad de tránsito. Comprendiendo el proceso de construcción identitaria del pueblo Tabatinguense, la investigación se orientó por aportes teóricos de la Antropología, Sociología, Filosofía, Arte y Sociolingüística. Partiendo de la premisa del análisis de la construcción identitaria del pueblo de Tabatinga, nuestra investigación tendrá un sesgo cualitativo, sin descartar los ítems cuantitativos que son necesarios para comprender los datos obtenidos, ya que son complementarios al trabajo en el campo de las ciencias sociales (MINAYO, 1996); (GOLDENBERG, 2015), así como la entrevista en profundidad (Bourdieu, 2007). La integración de la investigación cuantitativa y cualitativa permitirá cruzar conclusiones para tener mayor confianza en que los datos no son producto de un procedimiento específico o de una situación particular. De esta forma, fue bajo estos aspectos metodológicos que desarrollamos nuestra investigación buscando construir, lo más cerca posible, un marco interpretativo de la realidad en la que se inserta nuestro objeto de estudio, la construcción identitaria del pueblo tabatinguense.
Keywords: Identidade social - Tabatinga (AM); Tabatinga (AM) - Aspectos sociais; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS; Processos socioculturais; Fronteira; Identidade; Tabatinga/AM